The management approach for a large periapical lesion: a review / Nazrin Mohd Isa, Nurul Ain Ramlan and Afzan Adilah Ayoub - Mohd Isa, Nazrin; Ramlan, Nurul Ain; Ayoub, Afzan Adilah (Faculty of Dentistry, Universiti Teknologi MARA, 2024)
Endodontic therapy of large periapical lesions presents a substantial challenge to the clinician. The destruction of periapical tissues, including bone and adjacent structures, characterizes these lesions. A systematic approach that incorporates multiple treatment modalities for optimal healing is necessary for the effective management of such lesions. This article discusses the management strategy for large periapical lesions in endodontics, emphasizing the significance of accurate diagnosis, appropriate treatment planning, and the application of effective therapeutic techniques. It has been reported that endodontic therapy has a more favorable prognosis for minor lesions as opposed to larger lesions. A conservative approach, such as non-surgical root canal therapy, should be the initial course of action prior to surgical endodontic intervention.